Preparing the Welfare State: American Unemployment Reform in the Early Twentieth Century - Sautter, Udo (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1990)
AbstractEfforts have recently been made to trace the origins of some of the New Deal's programmes back to the Hoover administration. Activities to combat unemployment, however, have a prehistory beginning in the last third of the nineteenth century. Realizing that modern unemployment was an environmental rather than an individual problem, progressive reformers as well as bureaucrats endeavoured to find solutions. By the time of the entry of the United States into World War I, the major measures — counting, labour exchanges, public works, and unemployment insurance — had been devised and some testing had begun. The postwar years and the early 1920s served as a period of reflection and refinement. Rising unemployment from about 1927 on and, moreso, the onset of the Great Depression, gave opportunity to examine more thoroughly the instruments developed by then. Some fine-tuning occurred, and on his accession to the presidency F. D. Roosevelt found a ready-made instrumentarium to use.